New insights of the application of water or ethanol-water plant extract rich in active compounds in food - Plaskova, Anna; Mlcek, Jiri (Frontiers in Nutrition, 2023)
Plants are recognized as natural sources of antioxidants (e.g., polyphenols, flavonoids, vitamins, and other active compounds) that can be extracted by green solvents like water, ethanol, or their binary mixtures. Plant extracts are becoming more used as food additives in various food systems due to their antioxidant abilities. Their application in food increases the shelf life of products by preventing undesirable changes in nutritional and sensory properties, such as the formation off-flavors in lipid-rich food. This review summarizes the most recent literature about water or ethanol-water plant extracts used as flavors, colorings, and preservatives to fortify food and beverages. This study is performed with particular attention to describing the benefits of plant extract-fortified products such as meat, vegetable oils, biscuits, pastries, some beverages, yogurt, cheese, and other dairy products. Antioxidant-rich plant extracts can positively affect food safety by partially or fully replacing synthetic antioxidants, which have lately been linked to safety and health issues such as toxicological and carcinogenic consequences. On the other hand, the limitations and challenges of using the extract in food should be considered, like stability, level of purity, compatibility with matrix, price, sensory aspects like distinct taste, and others. In the future, continuous development and a tendency to use these natural extracts as food ingredients are expected, as indicated by the number of published works in this area, particularly in the past decade.